Efficacy of prophylactic dexamethasone in reducing post-embolization syndrome following transcatheter arterial chemoembolization for hepatocellular carcinoma: a systematic review and meta-analysis - Rongli Li; Zhen Huang; Yun Liu; Teng Li (BMC Gastroenterology)
Abstract Background and objectives Transcatheter arterial chemoembolization (TACE) is a fundamental treatment for unresectable hepatocellular carcinoma despite its tendency to induce postembolization syndrome (PES), which can negatively impact the quality of life and treatment outcomes of patients. This study aimed to evaluate the efficacy of prophylactic dexamethasone in reducing PES following TACE. Methods A thorough search across major databases was conducted to identify studies investigating the prophylactic use of dexamethasone in preventing and reducing PES. Efficacy was evaluated via a meta-analysis utilizing a random-effects model to determine the risk ratio (RR) and 95% confidence intervals (CIs), focusing on PES symptoms, including abdominal pain, fever, nausea, and vomiting. Results Among 406 meticulously reviewed studies, 5, encompassing a patient cohort of 400 individuals, were included in the final analysis. The results revealed a significant reduction in the overall incidence of abdominal pain (RR = 0.61; 95% CI: 0.51–0.75; P < 0.001), fever (RR = 0.46; 95% CI: 0.35–0.60; P < 0.001), and nausea and vomiting (RR = 0.57; 95% CI: 0.43–0.76; P < 0.001) using dexamethasone prophylactically. Conclusion This meta-analysis suggested that the prophylactic administration of dexamethasone effectively prevents and reduces PES, significantly reducing the incidence of key symptoms, including abdominal pain, fever, nausea, and vomiting.